Polish Adaptation and Normalization of Organizational Climate Questionnaire by Rosenstiel and Boegel - Durniat , Katarzyna (Studia Oeconomica Posnaniensia, 2018)
The paper presents a Polish validated and normalized version of a German organizational climate questionnaire, by L. Rosenstiel and R. Boegel (1992). The tool was adapted to Polish culture twice (I adaptation: Augustynowicz, 1997; N = 233; II adaptation: Durniat, 2005/6; N = 367) and normalized on a sample of Polish employees (Durniat, 2015, N = 976). The aim of the paper is to present the theoretical basis of the questionnaire, its structure, content and psychometric properties along with the rules of the tools' implementation and conversion of the raw tests' results into a normalized scale. The Polish shortened version of the instrument includes 55 items constituting 7 scales (α Cronbach ranging from 0.81 to 0.90). The tool allows to measure, in a quick and reliable manner, organizational climate and its factors, such as: style of management, organization of work, communication, cooperation, motivation and career development and social support. The questionnaire may be used by scientists and practitioners in social, organizational, psychological and managerial research focused on an organizational climate itself or its relation with other phenomena, such as: job satisfaction, work engagement, work efficacy, absenteeism, workplace stress, burnout, mobbing, etc. The paper includes a questionnaire with key, norms and rules of the test results' interpretation.